Complications of retrograde intrarenal surgery for the treatment of large renal stone burdens: A prospective observational study (Research, Society and Development, 2024)
Objective: Retrograde intrarenal surgery (RIRS) is a less invasive method of treating renal calculi. Despite its widespread use, there is little research on RIRS safety address large renal stone burdens (≥21 mm). This study sought to evaluate the perioperative complications associated with RIRS. Methodology: A prospective evaluation of stone characteristics and perioperative outcomes was conducted on 55 patients each having a stone burden of ≥21 mm and treated with RIRS between November 2019 and October 2021. Patients were divided into three groups according to stone burdens (21–30 mm, 31–40 mm, and >40 mm). Chemoprophylaxis and surgery were performed according to standard procedures. All of these patients were followed up on for a minimum of three months. Results: The mean stone burden was 32.36 ± 10.20 mm. The mean cumulative endoscopy time was 142.0 ± 74.7 min. The overall stone-free rate (SFR) was 78.2%, with an average of 1.58 sessions of RIRS. The majority of the post-operative complications were minor (Clavien-Dindo I and II). Clavien-Dindo IIIa complications reported in 9%. Conclusions: RIRS is a safe treatment alternative with low morbidity for addressing large renal stone burdens in a subset of patients who are unfit for other therapeutic options.